2011
DOI: 10.1093/neuonc/nor042
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cell accumulation and function in patients with newly diagnosed glioblastoma

Abstract: To assess the accumulation of myeloid-derived suppressor cells (MDSCs) in the peripheral blood of patients with glioma and to define their heterogeneity and their immunosuppressive function. Peripheral blood mononuclear cells (PBMCs) from healthy control subjects and from patients with newly diagnosed glioma were stimulated with anti-CD3/anti-CD28 and T cells assessed for intracellular expression of interferon (IFN)-γ. Antibody staining of PBMCs from glioma patients and healthy donors (CD33, HLADR, CD15, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
303
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(315 citation statements)
references
References 36 publications
8
303
1
3
Order By: Relevance
“…[23][24][25][26][27][28][29][30] It has been previously shown in human samples and experimental GBM models that MDSCs are powerful inhibitors of anti-tumor immune responses. 30,31 Through a variety of mechanisms that inhibit T cell activation and expansion, including the production of arginase and inducible nitric oxide synthase (iNOS), reactive oxygen species and/or reactive nitrogen species (ROS and/or RNS), release of IL-10, expansion of regulatory T cells (Tregs), and inhibition of T cell migration, MDSCs have been shown to promote immunosuppression and tumor progression. [32][33][34][35][36] Targeting specific mechanisms of immune suppression are critical to increasing the effectiveness of immunotherapies.…”
Section: Malignant Brain Tumors (Gliomasmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] It has been previously shown in human samples and experimental GBM models that MDSCs are powerful inhibitors of anti-tumor immune responses. 30,31 Through a variety of mechanisms that inhibit T cell activation and expansion, including the production of arginase and inducible nitric oxide synthase (iNOS), reactive oxygen species and/or reactive nitrogen species (ROS and/or RNS), release of IL-10, expansion of regulatory T cells (Tregs), and inhibition of T cell migration, MDSCs have been shown to promote immunosuppression and tumor progression. [32][33][34][35][36] Targeting specific mechanisms of immune suppression are critical to increasing the effectiveness of immunotherapies.…”
Section: Malignant Brain Tumors (Gliomasmentioning
confidence: 99%
“…shown that cancer progression can be retarded or reversed with the removal of MDSCs [82,83], more studies are needed in procuring an effective way of mitigating their suppressive effects in cancer.…”
Section: Mdscs In Cancermentioning
confidence: 99%
“…[5][6][7] MDSCs express CD34, common myeloid marker CD33, macrophage/DC marker CD11b, and IL-4R␣ (CD124), but lack expression of the lineage (Lin) markers of DCs and other mature myeloid cells. 7,8 Human MDSCs are defined as CD33 ϩ Lin Ϫ HLA-DR Ϫ/low or CD33 ϩ CD14 Ϫ HLA-DR Ϫ , with recent studies demonstrating a CD14 ϩ CD11b ϩ HLA-DR low phenotype of monocytic MDSCs in melanoma, 9 prostate cancer, 10 gastrointestinal malignancies, 11 hepatocellular carcinoma, 12, 13 and glioblastoma, 14 in addition to a CD15 ϩ population of neutrophil-related immature MDSCs of similar biologic activity present in the peripheral blood. 7 MDSCs express high levels of immunosuppressive factors such as indoleamine dioxygenase (IDO), 15,16 IL-10, 8 arginase, 17,18 inducible nitric oxide synthase (NOS2), 18 nitric oxide, and reactive oxygen species, 19 and use these molecules to suppress T-cell responses, 20,21 whereas their induction of natural killer cell anergy and reduced cytotoxicity is arginase independent 12 but depends on TGF␤ 1.…”
Section: Introductionmentioning
confidence: 99%